2022
DOI: 10.3390/cells11030373
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Amyloid Instigates Dysfunction of Mitochondria in Cardiac Cells

Abstract: Alzheimer’s disease (AD) includes the formation of extracellular deposits comprising aggregated β-amyloid (Aβ) fibers associated with oxidative stress, inflammation, mitochondrial abnormalities, and neuronal loss. There is an associative link between AD and cardiac diseases; however, the mechanisms underlying the potential role of AD, particularly Aβ in cardiac cells, remain unknown. Here, we investigated the role of mitochondria in mediating the effects of Aβ1-40 and Aβ1-42 in cultured cardiomyocytes and prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The pulmonary vein contains abundant amyloid peptides and directly influences atrial remodeling as a major substrate of AF [ 35 ]. Moreover, cardiac dysfunction of AD model mice and cytotoxicity of Aβ to cardiomyocytes have been reported [ 24 , 36 , 37 ]. Our study and others have reported that mitochondrial oxidative stress plays a pivotal role in the pathogenesis of both AD and AF [ 20 , 38 ], which could be attributed to Ca 2+ overload, ROS generation and energy deprivation [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pulmonary vein contains abundant amyloid peptides and directly influences atrial remodeling as a major substrate of AF [ 35 ]. Moreover, cardiac dysfunction of AD model mice and cytotoxicity of Aβ to cardiomyocytes have been reported [ 24 , 36 , 37 ]. Our study and others have reported that mitochondrial oxidative stress plays a pivotal role in the pathogenesis of both AD and AF [ 20 , 38 ], which could be attributed to Ca 2+ overload, ROS generation and energy deprivation [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Re-dissolved the lyophilized amyloid-β in DMSO and diluted it to 1 mM in deionized water. After incubating at 4 °C for 48 h to form oligomers, amyloid-β was diluted in culture media to the final concentration of 50 μM [ 24 ]. Then, HL-1 cells were administrated by Aβ after serum starvation, and cells in control group were treated with same volume of DMSO at 0.1% (v/v) in deionized water.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondria, as the center of cellular energy metabolism, is involved in a variety of signaling pathways and regulates cellular function and survival [36]. After mitochondria is exposed to adverse stimulation, it will occur multiple harmful changes such as increased oxidative stress, swelling and deformation, and decreased membrane potential [37,38]. These changes can lead to in ammasome activation, cell senescence and death, which plays a crucial role in some degenerative diseases [39].…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, an increase in ABAD was associated with reduced respiratory responses in both sub-sarcolemmal and inter-myofibrillar mitochondria 60 and increased injury in response to ischemia/reperfusion 61 . Furthermore, exposure of isolated rat heart mitochondria or immortalised H9C2 cardiomyoblasts to Aβ 42 causes mitochondrial dysfunction, not only affecting energetics but also resulting in elevated ROS production, a loss of mitochondrial membrane potential, mitochondrial swelling, and impaired capacity to retain calcium 62 . In contrast, Aβ 40 had less pronounced effects on these parameters of mitochondrial function 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, exposure of isolated rat heart mitochondria or immortalised H9C2 cardiomyoblasts to Aβ 42 causes mitochondrial dysfunction, not only affecting energetics but also resulting in elevated ROS production, a loss of mitochondrial membrane potential, mitochondrial swelling, and impaired capacity to retain calcium 62 . In contrast, Aβ 40 had less pronounced effects on these parameters of mitochondrial function 62 . Together, these findings support our conclusion that the effects of Aβ 42 on the heart are in part due to the internalisation of Aβ 42 , but not Aβ 40 , by cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%